The structure of SAV1646 from Staphylococcus aureus belonging to a new `ribosome‐associated' subfamily of bacterial proteins. (1st February 2015) - Chirgadze, Yuri N.; Clarke, Teresa E.; Romanov, Vladimir; Kisselman, Gera; Wu‐Brown, Jean; Soloveychik, Maria; Chan, Tiffany S. Y.; Gordon, Roni D.; Battaile, Kevin P.; Pai, Emil F.; Chirgadze, Nickolay Y.
<x xml:space="preserve">Abstract</x> The crystal structure of the SAV1646 protein from the pathogenic microorganism Staphylococcus aureus has been determined at 1.7 Å resolution. The 106‐amino‐acid protein forms a two‐layer sandwich with α/β topology. The protein molecules associate as dimers in the crystal and in solution, with the monomers related by a pseudo‐twofold rotation axis. A sequence‐homology search identified the protein as a member of a new subfamily of yet uncharacterized bacterial `ribosome‐associated' proteins with at least 13 members to date. A detailed analysis of the crystal protein structure along with the genomic structure of the operon containing the sav1646 gene allowed a tentative functional model of this protein to be proposed. The SAV1646 dimer is assumed to form a complex with ribosomal proteins L21 and L27 which could help to complete the assembly of the large subunit of the ribosome.